2013
DOI: 10.1111/ijau.12015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Personal and Organizational Factors on Role Ambiguity amongst Internal Auditors

Abstract: Increasing concerns about company failures has given rise to the significant role of risk management in organizations. The Institute of Internal Auditors (IIA) has introduced a new framework which specifies that internal auditors' responsibilities include managing risks. This change from traditional to modern obligation may cause internal auditors to be uncertain regarding this function. This study investigates the effects of personal and organizational factors on role ambiguity amongst internal auditors in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
4
35
1
2
Order By: Relevance
“…Results of previous studies show that role conflict and role ambiguity occur in external auditors in public accounting firms in Australia (Chong and Monroe, 2015), United States (Jones et al, 2012;Jones et al, 2010;Viator, 2001), Thailand (Ussahawanitchakit, 2008), and New Zealand (Fisher, 2001). Results of previous studies also show that role conflict and role ambiguity occurs in internal auditors in companies listed on the Malaysian stock exchange (Aghghaleh et al, 2014;Ahmad and Taylor, 2009) and internal auditors who are members of the American Institute of Certified Public Accountants (Larson, 2004). Role conflict may arise for local government internal auditors because of their role in providing audit oversight to local government agencies as well as providing consulting services to the management of local government agencies.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Results of previous studies show that role conflict and role ambiguity occur in external auditors in public accounting firms in Australia (Chong and Monroe, 2015), United States (Jones et al, 2012;Jones et al, 2010;Viator, 2001), Thailand (Ussahawanitchakit, 2008), and New Zealand (Fisher, 2001). Results of previous studies also show that role conflict and role ambiguity occurs in internal auditors in companies listed on the Malaysian stock exchange (Aghghaleh et al, 2014;Ahmad and Taylor, 2009) and internal auditors who are members of the American Institute of Certified Public Accountants (Larson, 2004). Role conflict may arise for local government internal auditors because of their role in providing audit oversight to local government agencies as well as providing consulting services to the management of local government agencies.…”
Section: Introductionmentioning
confidence: 94%
“…The results showed that formalization 69 is negatively related to role ambiguity. Aghghaleh (2014) examined the relationship between mechanistic structure organizations (organizations with a high degree of formalization) with role ambiguity for internal auditors in private companies. The results indicate that a mechanistic organizational structure is negatively related to role ambiguity.…”
Section: Formalization and Role Ambiguitymentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of auditors are aged between 36 and 45, and higher education has now increased to over 92% (Aghghaleh, Mohamed, & Ahmad, 2015;IIA, 2015). Professional experience is concentrated between 11 and 20 years, whereas in Europe and worldwide (CBOK: IIA) the average is around 10 years.…”
Section: Sample and Data Collectionmentioning
confidence: 99%